Deep learning as a learning strategy in islamic religious education (PAI) in schools: A literature review - Siti Rahma; Irjus Indrawan; Maimunah Maimunah (Institute of Computer Science (IOCS), 2026)
Despite the growing adoption of deep learning in contemporary education, limited studies have examined its conceptual integration into Islamic Religious Education (PAI), creating a need for a comprehensive theoretical analysis. This study investigates and explains the application of deep learning as a learning strategy within Islamic Religious Education (PAI) and its relevance to students' learning experiences. Employing a library research approach, the study draws upon a range of scholarly publications, books, educational policy documents, and previous research findings related to the concepts of deep learning and Islamic Religious Education. The collected data were examined through a systematic process involving identification, classification, interpretation, and synthesis of information obtained from multiple sources. The analysis demonstrates a strong alignment between the principles of deep learning and the objectives of Islamic Religious Education. Both emphasize the development of comprehensive understanding, reflective thinking, and the internalization of Islamic values. Deep learning encourages the integration of cognitive, affective, and psychomotor dimensions through reflective, problem-centered, contextual, collaborative, and experiential learning practices. In addition, its implementation contributes to the strengthening of critical thinking abilities, religious awareness, and practical life skills that enable learners to respond more effectively to contemporary challenges, including technological developments, changing learning systems, educational assessment practices, and policy transformations. The study further reveals that deep learning has become a central concern in educational reform efforts, particularly in relation to the implementation of educational policies promoted by the 21st-century learning paradigm and the Deep Learning Policy introduced by the Ministry of Primary and Secondary Education. The findings provide a conceptual framework for understanding the development of Islamic Religious Education learning strategies that are more adaptive, relevant, and responsive to contemporary educational needs.